Assessing groundwater quality using water quality index in semiarid region of Aurangabad district, central India - R. Aher, K.; L. Salve, P.; G. Gaikwad, S. (International Journal of Advanced Geosciences, 2020)
This paper presents a study on the influence of geochemical parameters on groundwater quality in GV-35 watershed of Aurangabad district, Maharashtra, India. Groundwater samples were collected from different locations and their physiochemical quality parameter were analysed. Water quality index (WQI) was determined on the basis of various physical and chemical parameters like pH, electrical conductivity, turbidity, total dissolved solids, total hardness, calcium, magnesium, sulphate, chloride, nitrate, sodium, potassium, carbonate, bicarbonate, fluoride and iron. These parameters were determined for the calculation of water quality index (WQI). During pre-monsoon, 4% of groundwater samples were excellent, 65% were good; 26 % were poor; and 4% were unsuitable for domestic suitability, whereas in post-monsoon, 65% of water samples were good; 26% were poor; 4% were very poor and 4% were unsuitable for domestic suitability .Â Â Â Â